Juridical Analysis on the Elimination of Race and Ethnic Discrimination in Making Certificate of Inheritance in the Land Registration Process Based on Law Number 40 of 2008 - Nurdia, Fita Candra; Soediro, Soediro; Hidayah, Astika Nurul (UMPurwokerto Law Review, 2021)
The classification of the population in Indonesia has occurred since the days of the Dutch East Indies, which is regulated in Article 163 IS. The regulation of population classification is still applied in the making of the Inheritance Certificate for Indonesian citizens, which is now regulated in the Regulation of the State Minister for Agrarian Affairs / Head of the National Land Agency No. 3 of 1997 concerning the Implementation of Government Regulation no. 24 of 1997 concerning Land Registration. The existence of these regulations creates acts of discrimination that are against Pancasila, legal principles, and laws. This research uses a normative juridical approach, namely by reviewing or analyzing secondary data in the form of literature, journals, and laws and regulations. Based on the results of research in the making of an inheritance certificate, there is still discrimination because it is based on the division of 3 (three) population groups, namely the European group, the Bumiputera group, and the Foreign Eastern group, thus this is not in line with the provisions of Law Number 40 of 2008 concerning the Elimination of Racial Discrimination and ethnicity because Indonesian citizens are entitled to equal positions before the law. Keywords: Classification, Inheritance Certificate, Discrimination